TRANSITIONAL DYNAMICS OF DHAKA STOCK EXCHANGE: ANALYSIS FROM PRE-LOCKDOWN TO POST-REOPENING - Karim, Arif; Jamal, Ahmed; Ioannou, Christos; Agha, Mohammad; Agha , Reema (Ayden International Journal of Banking, Finance and Technology, 2024)
This study delves into the unprecedented disruption caused by the COVID-19 pandemic in financial markets, specifically exploring the impact on the Dhaka Stock Exchange (DSE) in Bangladesh. The pandemic, originating from the novel coronavirus, instigated global turmoil, redefining the dynamics of financial landscapes. The outbreak's rapid progression led to an urgent need for comprehensive investigation into the alterations it wrought upon stock markets. The concept of disease extends beyond physical injury, encompassing structural and functional disorders within biological organisms. An affliction assumes pandemic proportions when it engulfs extensive regions and populations. Conversely, an epidemic pertains to widespread regional impact. This research capitalizes on these epidemiological distinctions to scrutinize the ramifications of the COVID-19 pandemic on the DSE, a vital financial institution. Triggered by the World Health Organization's declaration of the coronavirus outbreak as a pandemic on March 11, 2020, global markets witnessed unprecedented shocks. A profound disruption occurred on March 12, 2020, with the Dow plummeting by 9.99%, an unprecedented decline comparable only to the 1929 Black Monday crash. This marked the beginning of a sustained period of market volatility that reverberated across economies. Against this backdrop, governments resorted to drastic measures including lockdowns, travel restrictions, and business closures to mitigate the virus's impact. By meticulously analyzing the DSE's response to the pandemic, this study addresses pivotal questions surrounding the shift in risk-return profiles of individual stocks and sectors during the pandemic and lockdown period. Notably, the DSE distinguished itself by opting for a comprehensive shutdown from March 26 to May 30, 2020, to stave off collapse. This decision introduced an intriguing scenario for assessing market behavior and risk-return dynamics.